Enhanced and specific epoxidation activity of P450 BM3 mutants for the production of high value terpene derivatives. Issue 52 (28th November 2022) - Correddu, Danilo; Helmy Aly, Sabrina; Di Nardo, Giovanna; Catucci, Gianluca; Prandi, Cristina; Blangetti, Marco; Bellomo, Chiara; Bonometti, Elisabetta; Viscardi, Guido; Gilardi, Gianfranco
Abstract : Laboratory evolved P450 BM3 A2 has an increased activity on the oxidation of high value terpenes. The oxidation of linalool into linalool oxide by P450 BM3 is shown for the first time. Abstract : Terpenes are natural molecules of valuable interest for different industrial applications. Cytochromes P450 enzymes can functionalize terpenoids to form high value oxidized derivatives in a green and sustainable manner, representing a valid alternative to chemical catalysis. In this work, an enhanced and specific epoxidation activity of cytochrome P450 BM3 mutants was found for the terpenes geraniol and linalool. This is the first report showing the epoxidation of linalool by P450 BM3 and its mutant A2 (Asp251Gly/Gln307His) with the formation of valuable oxide derivatives, highlighting the relevance of this enzymes for industrial applications.